Simultaneous energy generation, decolorization, and detoxification of the azo dye Procion Red MX-5B in a microbial fuel cell - de Almeida, Erica Janaina Rodrigues [UNESP] (2021)
Microbial fuel cells (MFCs) are sustainable technologies that can effectively treat wastewater with simultaneous electricity generation. The present study investigated the performance of an MFC highly specific for decolorizing and degrading the azo dye Procion Red MX-5B (PRMX), which eliminates the toxicity of the solution while generating electricity. The MFC anode biofilm was formed from mining sediment after acclimatization in sodium acetate (1 g L-1), followed by the addition of 100 mg L-1 PRMX. The system was totally decolorized, and the color removal occurred fast during the first 70 h of the MFC feed cycle. Total mineralization occurred after 172 h of the feed cycle of the MFC system. Complete degradation of the aromatic intermediates generated after PRMX degradation reduced the toxic potential of the PRMX solution against A. salina larvae and L. sativa seeds to near zero. PRMX supply into the anode increased the voltage output from 360 mV (1 g L-1 sodium acetate - SA) to 520 mV (PRMX/SA 100 mg L-1: 0.25 g L-1). The maximum power density of 156 mW m-2 obtained herein was higher than most values reported for dye remediation in similar devices. Assessment of the microbial community showed that PRMX addition to the acetate diminished the microbial diversity in the bioanode. Pseudomonas and Dysgonomonas accounted for 87% of the biofilm. Therefore, both genera are most probably responsible for external electron transfer and PRMX degradation.